The Effects of Running Cadence Manipulation on Plantar Loading in Healthy Runners - Wellenkotter, J.; Kernozek, T. W.; Meardon, S.; Suchomel, T. (International Journal of Sports Medicine, 2014)
Our purpose was to evaluate effects of cadence manipulation on plantar loading during running. Participants (n=38) ran on a treadmill at their preferred speed in 3 conditions: preferred, 5% increased, and 5% decreased while measured using in-shoe sensors. Data (contact time [CT], peak force [PF], force time integral [FTI], pressure time integral [PTI] and peak pressure [PP]) were recorded for 30 right footfalls. Multivariate analysis was performed to detect differences in loading between cadences in the total foot and 4 plantar regions. Differences in plantar loading occurred between cadence conditions. Total foot CT and PF were lower with a faster cadence, but no total foot PP differences were observed. Faster cadence reduced CT, pressure and force variables in both the heel and metatarsal regions. Increasing cadence did not elevate metatarsal loads; rather, total foot and all regions were reduced when healthy runners increased their cadence. If a 5% increase in cadence from preferred were maintained over each mile run the impulse at the heel would be reduced by an estimated 565 body weights*s (BW*s) and the metatarsals 140–170 BW*s per mile run despite the increased steps taken. Increasing cadence may benefit overuse injuries associated with elevated plantar loading.
Keywords: pressure; biomechanics; kinetics; cadence; running; overuse injury